化简1+x+x(1+x)+x(1+x)^2+.+x(1+x)^2003,得到

来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 22:38:46
化简1+x+x(1+x)+x(1+x)^2+.+x(1+x)^2003,得到化简1+x+x(1+x)+x(1+x)^2+.+x(1+x)^2003,得到化简1+x+x(1+x)+x(1+x)^2+.+

化简1+x+x(1+x)+x(1+x)^2+.+x(1+x)^2003,得到
化简1+x+x(1+x)+x(1+x)^2+.+x(1+x)^2003,得到

化简1+x+x(1+x)+x(1+x)^2+.+x(1+x)^2003,得到
1+x+x(1+x)+x(1+x)^2+……+x(1+x)^2003
=1*(1+x)+x(1+x)+x(1+x)^2+……+x(1+x)^2003
=(1+x)^2+x(1+x)^2+……+x(1+x)^2003
=1*(1+x)^2+x(1+x)^2+……+x(1+x)^2003
=(1+x)*(1+x)^2+……+x(1+x)^2003
=(1+x)^3+……+x(1+x)^2003
……
=(1+x)^2004

1后面的2004项是以x为首项1+x为公比的等比数列